CORROSION AND SURFACE PROTECTION IN MACHINE MATERIALS FRICTION HAVE DIFFERENT SURFACE PAIRS EXPERIMENTAL INVESTIGATION OF FACTORS - Senai YALCINKAYA (Fiabilitate şi Durabilitate)
Friction force, normal force, linear change. The normal force varies with the loads on the friction object. In order to determine the friction force and the friction coefficient, the friction object and the friction speed are used. The experimental work was carried out in three stages. In the first stage, the effect of normal force on the friction force was studied. In the second step, the friction force of the friction surface area is influenced. The effect of the change of the shear rate in step 3 on the friction force was investigated. At the last stage, the experimental study of the effect of the material selection on the friction force was made and it was seen that the aluminum / brass surface pair had the smallest friction coefficient as a result of the opening. The greatest coefficient of friction is found in the pair of glass / felt objects.